NUTRITIONAL/CHEMICAL CONSTITUENTS, GROWTH PERFORMANCE AND ANTHROPOMETRIC ANALYSIS OF Adansonia digitata LEAVE-BASED DIET IN FEMALE RATS - Abiodun, Oyegoke Rukayat; Abdulwahab, Aminat Abebi; Jumoke, Musa Fasilat; Osifade, Jahswill Toluwanimi; Nafiu, Mikhail Olugbemiro; Moronfolu, Ibrahim Adeola (Science Journal of University of Zakho, 2025)
The nutritional benefits of most of our extinction underutilized edible plants cannot be underrated. However, there is the need to quantity their nutrients and estimate the amount our body requires to function effectively. Therefore, the nutritional constituents and assessments of Adansonia digitata (A. digitata) leave-based diet were evaluated in rats. Fifty rats were grouped into five and were fed on a basal diet, 25%, 50%, 75%, and 100%- inclusion, respectively. The constituents, Feed Conversion Ratio (FCR), Body Weight Gain (BWG), Feed intake (FI), Body Mass Index (BMI), Abdominal, Arm Circumferences, and animal length were estimated using standard methods. Proximate revealed high fiber and carbohydrate contents. Calcium, Vitamin C/E, saponin, and tannins were the most abundant. No notable difference (p < 0.05) was observed in the BWG and FI when 25% and 50% inclusion were compared with the control. For the BMI, all groups showed significant differences when initial values were compared with the final. At the same time, for the abdominal circumference (AC), Arm Circumference (ArC), and naso-anal length, there was no notable difference between 75% and 100%. Overall, the results indicate that the leaves possess good nutritional constituents and can be incorporated into our diet at 25% and 50% inclusions to achieve excellent nutrition and body metabolism.